2018
DOI: 10.17576/jskm-2018-15
|View full text |Cite
|
Sign up to set email alerts
|

Acute Modulatory Effects of Apple Cider Vinegar, Garlic, Ginger, Lemon and Honey Mixture, with and Without Exercise on Postprandial Glycemia in Non-Diabetic Females

Abstract: Postprandial hyperglycemia is independently related to cardiovascular disease. Garlic, ginger, lemon, honey and apple cider vinegar are known to have anti-glycemic properties. However, the effectiveness of combination of these natural products on reducing postprandial glycemia is uncertain. The aim of the present study was to investigate the glucoselowering effect of a novel mixture consisting of apple cider vinegar, garlic, ginger, lemon, and honey; alone and in combination with exercise in response to a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
4
Order By: Relevance
“…Some previous studies showed promising effects of the mixture in improving the lipid profile in hyperlipidemia-induced animal models when orally fed or incorporated in the diet [ 15 , 16 ]. It also showed a good result in delaying and lowering postprandial glucose when administered alone or accompanied by exercise in non-diabetic human females after a high carbohydrate meal compared to the control group [ 17 ]. Ishak et al [ 17 ] noted the glucose changes were 8% in the mixture group, 13% in the exercise group and 15% in the mixture accompanied with the exercise group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies showed promising effects of the mixture in improving the lipid profile in hyperlipidemia-induced animal models when orally fed or incorporated in the diet [ 15 , 16 ]. It also showed a good result in delaying and lowering postprandial glucose when administered alone or accompanied by exercise in non-diabetic human females after a high carbohydrate meal compared to the control group [ 17 ]. Ishak et al [ 17 ] noted the glucose changes were 8% in the mixture group, 13% in the exercise group and 15% in the mixture accompanied with the exercise group.…”
Section: Introductionmentioning
confidence: 99%
“…It also showed a good result in delaying and lowering postprandial glucose when administered alone or accompanied by exercise in non-diabetic human females after a high carbohydrate meal compared to the control group [ 17 ]. Ishak et al [ 17 ] noted the glucose changes were 8% in the mixture group, 13% in the exercise group and 15% in the mixture accompanied with the exercise group. Despite some promising results, the mechanisms that underlay the activities remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial hypolipidemic effects of natural honey, a rich source of antioxidants and nutritional elements have been scarcely studied. Therefore, Ishak et al [181] investigated the effect of a mixture consisting of apple cider vinegar, garlic, ginger, lemon, and honey in lowering glucose levels in non-diabetic individuals who performed or not exercises. The individuals were also subjected to a high-carbohydrate meal.…”
Section: Anti-atherogenic Effectmentioning
confidence: 99%
“…Preparation of polyphenol-rich mixture (PRM) was done according to Ishak et al (2018), with a slight modification on the ratio. Lemon, garlic, ginger was first juiced using a juicer (ELBA EJE71A043lWH, Kuala Lumpur, Malaysia).…”
Section: Sample Preparationmentioning
confidence: 99%
“…The herbal mixture consists of ginger, garlic, apple cider, lemon and honey (PRM) was previously reported to reduce triglyceride levels in hyperlipidemia-induced rats and had a hepatoprotective effect on the liver (Naseem et al, 2016). In addition, this mixture was shown to reduce postprandial glucose in non-diabetic human females, alone or together with exercise (Ishak et al, 2018). Even though there were few studies conducted on this herbal mixture, there is still a lack of information in regard to its safety dosage and its phytochemicals that may contribute to their bioactivity.…”
Section: Introductionmentioning
confidence: 99%